2014
DOI: 10.1136/injuryprev-2013-041138
|View full text |Cite
|
Sign up to set email alerts
|

ATV riding and helmet use among youth aged 12–17 years, USA, 2011: results from the YouthStyles survey

Abstract: BackgroundNational estimates of all-terrain vehicle (ATV) riding patterns among youth in the USA are lacking.MethodsWe analysed the 2011 YouthStyles survey to estimate the proportion of 12–17 year olds in the USA who had ridden an ATV at least once during the past 12 months and summarise their patterns of helmet use.ResultsOf the 831 youth respondents, an estimated 25% reported riding an ATV at least once during the past year. The proportion of youth living outside of a Metropolitan Statistical Area who report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
(35 reference statements)
1
17
1
Order By: Relevance
“…18 Although lifesaving, routine helmet use by children occurs <50% of the time, recent literature suggests. 35 Additionally, although helmets are successful in the prevention of trauma to the head and neck, crush injuries from rollovers onto smaller children have not been impacted by helmet laws. 36,37 Age restrictions were missing from state ORV laws before the early 1990s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Although lifesaving, routine helmet use by children occurs <50% of the time, recent literature suggests. 35 Additionally, although helmets are successful in the prevention of trauma to the head and neck, crush injuries from rollovers onto smaller children have not been impacted by helmet laws. 36,37 Age restrictions were missing from state ORV laws before the early 1990s.…”
Section: Discussionmentioning
confidence: 99%
“…This is significant in that orthopedic and crush injuries from rollovers on to smaller children are thought to contribute significantly to morbidity. 35,36,41 Vehicles with larger engines that are designed for adults have been consistently shown to increase the risk for fatalities and injuries in children. 42,43 After the implementation of the engine size restriction in Massachusetts, the rate of ED visits fell by 39% from 52 to 32 per 100 000 persons in the 14-to 17-year-old age group.…”
Section: Figurementioning
confidence: 99%
“…It is also of interest to consider reasons for observed change in incidence and distribution of injury over time. For example, a national study of injury rates (per 100,000 youth) for paediatric ATV-related injuries showed an increased rate from 50 to 67 (2001 vs. 2004) followed by a decrease to 42 by 2010 (Shults & West, 2015). The reasons for the decrease in deaths and injuries seen after the peak years remain unknown but may reflect the growing popularity of recreational off-road vehicles (Denning & Jennissen, 2018).…”
Section: When Does Injury Occur?mentioning
confidence: 99%
“…Studies repeatedly show that carrying passengers is a common riding practice [4,6,12,13,15,17,31]. However, although some riders are no doubt aware that most ATVs are designed for a single rider, this knowledge is by no means universal [16,32].…”
Section: Educationmentioning
confidence: 99%